It wasn’t so hard to find… new records of lyncodon patagonicus (de blainville, 1842) (mammalia, carnivora, mustelidae) in La Rioja Province, Argentina - Fariñas Torres, Thamara (2020)
The Patagonian weasel, Lyncodon patagonicus, is one of the least known carnivorous species of South America. Specifically for La Rioja province, there are only two reports of the species that date from the beginning of the 20th century. We describe new records of this species for this province that corresponds to the first records of L. patagonicus for La Rioja in more than 80 years. Moreover, the distribution of the species in La Rioja is expanded to an area within the ecoregion of "Monte de Sierras y Bolsones" that showed high probability values of presence on previous studies of potential distribution.